2011
DOI: 10.2495/safe-v1-n2-162-181
|View full text |Cite
|
Sign up to set email alerts
|

Property level flood adaptation measures: a novel approach

Abstract: Despite increased investment in flood defences, it is not economically viable to protect all at risk properties from the threat of flooding. This has led to a move towards encouraging property owners to take their own steps in making their homes or businesses less vulnerable to flooding. For example, the UK Government has introduced a grant aid scheme to encourage property level flood protection and has called for the development of new innovative flood approaches and products. Examining the effectiveness of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Property level flood risk adaptation measures refer to all actions available to homeowners to adapt their properties to flood risk (Joseph et al, 2011b) and involves the process of adjustment of households behaviours to actual or expected flood risk in order to reduce its impacts on households (IPCC, 2012). These include collective process of either keeping water out -resistance measures or allowing the water into the property but reducing the damage caused to the fabric of the property -resilience measures (ABI, 2003, Thurston et al, 2008, Beddoes and Booth, 2011, Wassell et al, 2009, Joseph et al, 2011b, Warren et al, 2011, JBA, 2012, Royal Haskoning, 2012, thereby allowing quick reinstatement of the property after flood water has receded. In addition, property can be adapted to flood risk by relocating expensive items from ground floor to upper floor or by registering for flood alert warning (Walker et al, 2008, Priest et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Property level flood risk adaptation measures refer to all actions available to homeowners to adapt their properties to flood risk (Joseph et al, 2011b) and involves the process of adjustment of households behaviours to actual or expected flood risk in order to reduce its impacts on households (IPCC, 2012). These include collective process of either keeping water out -resistance measures or allowing the water into the property but reducing the damage caused to the fabric of the property -resilience measures (ABI, 2003, Thurston et al, 2008, Beddoes and Booth, 2011, Wassell et al, 2009, Joseph et al, 2011b, Warren et al, 2011, JBA, 2012, Royal Haskoning, 2012, thereby allowing quick reinstatement of the property after flood water has receded. In addition, property can be adapted to flood risk by relocating expensive items from ground floor to upper floor or by registering for flood alert warning (Walker et al, 2008, Priest et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Relocation is often impractical and the option of building in areas of low or no flood risk is a planning issue, which must be addressed prior to construction [10,11]. Therefore, it is often the case that homeowners need to deal with flooding issues themselves and are simply left with a choice of several flood resistance and resilience options to protect their homes [12]. Flood resistance involves the construction of a building in such a way as to prevent floodwater entering the property and damaging its fabric [13].…”
Section: Property Level Flood Protectionmentioning
confidence: 99%
“…Since flooding cannot be prevented entirely, implementing flood mitigation measures is critical to minimize property-level flood disruption (Beddoes & Booth, 2011). Several studies have shown the reduction of flood damage with mitigation measures.…”
Section: Introductionmentioning
confidence: 99%